2018
DOI: 10.4062/biomolther.2017.146
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine Reduces Caffeine-Induced Sleep Disturbances and Excitation in Mice

Abstract: Worldwide, caffeine is among the most commonly used stimulatory substances. Unfortunately, significant caffeine consumption is associated with several adverse effects, ranging from sleep disturbances (including insomnia) to cardiovascular problems. This study investigates whether treatment with the Evodia rutaecarpa aqueous extract (ERAE) from berries and its major molecular component, evodiamine, can reduce the adverse caffeine-induced sleep-related and excitation effects. We combined measurements from the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…The orally administrated diphenhydramine hydrochloride (DIPH, 20 mg/mL, Sigma), an antihistamine with sleep aid effects, was used in the drug control group. Caffeine (15 mg/mL, Sigma) was intraperitoneally injected 30 min before the pentobarbital-induced sleep test to induce sleep disturbance in mice [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…The orally administrated diphenhydramine hydrochloride (DIPH, 20 mg/mL, Sigma), an antihistamine with sleep aid effects, was used in the drug control group. Caffeine (15 mg/mL, Sigma) was intraperitoneally injected 30 min before the pentobarbital-induced sleep test to induce sleep disturbance in mice [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…Unphosphorylated NF-κB fails to regulate the expression of inflammatory mediators above [96]. Additionally, Ko and his team compared Evo with L-NAME (an NOS inhibitor) and found that Evo can significantly Isoquinoline alkaloid BBR Water decoction Inhibits AChE, BChE activity and β-secretase [75] Indole alkaloids Evo Hot water reflux extraction Inhibits AChE [76] Terpenoids alkaloids Voacangine 90% ethanol reflux extraction Inhibits AChE [77] Steroidal alkaloids Conessine 90% ethanol extraction Inhibits AChE and the activation of NF-κB [78] Corynoxine 70% ethanol reflux extraction Reduce Ca2+ overload and tau protein hyperphosphorylation [79] Other alkaloids Caffeine Ethanol extraction Reduce caspase-3 and β-secretase [80] Isorhynchophylline 70% ethanol reflux extraction Down-regulate GSK-3β activity and activation of PI3K/Akt signaling pathway [79,81,82] reduce NO production and iNOS protein expression in mouse microglia, likely due to its regulation of interferon IFN-γ-related events [83]. To sum up, Evo can alleviate the pathological symptoms of AD in several ways.…”
Section: Evodiaminementioning
confidence: 99%
“…However, only exceedingly high caffeine blood concentrations, up to 150 mg/kg (equivalent to 50 caffeine pills or 1 tablespoon of powdered caffeine), are fatal and could lead to electrolyte imbalance, cardiac and circulatory deficits and death (Beauchamp et al, 2017). Caffeine is a central nervous system excitant (Ko et al, 2018) that is used in treatment of respiratory diseases and apnoea-related symptoms in newborns (Dobson & Hunt, 2013).…”
Section: F I G U R Ementioning
confidence: 99%